Level of Learning Independence And Factors Affecting Madrasah Aliyah Students In Distance Learning - Janes Jainueakhma; Ida Herwati; Muhasim Muhasim (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2022)
Teaching and learning activities from home have been carried out in schools in Indonesia. During the implementation of this policy, many parties felt the negative impact. One of the affected parties is that students feel that distance learning is a burden that causes psychic diseases. So that parents feel very troubled through this virtual activity. The purpose of this study is to find out the level of student independence and what factors affect students' learning independence. This research uses quantitative descriptive methods. The population of this study is the entire MA KH students. Moh Said Kepanjen with purposive sampling technique.  Data collection uses questionnaires with a liker scale. Data analysis uses frequency distribution to measure independence levels and t tests to analyze influencing factors. The results showed that 22 respondents or 73.3% of respondents had high learning independence. And there are the first two most influential factors, genetics and parenting and the education system. From the results of this study, it is expected to be a reference to increase students' independence in distance learning